Yet Another Hardware Implementation of Modular Multiplication - Nedjah, Nadia; Mourelle, Luiza de Macedo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
Modular multiplication is fundamental to several publickey cryptography systems such as the RSA encryption system. lt is also the most dominant part of the computation performed in such systems. The operation is time consuming for large operands. This paper examines the characteristics of yet another architecture to implement modular multiplication. An experimental modular multiplier prototype is described and some simulation results are presented.